THE STRATEGY FOR FISHERMEN HOUSEHOLD TO SURVIVE IN FACING POVERTYIN BAGAN BARAT VILLAGEBANGKO DISTRICTROKAN HILIR REGENCY RIAUPROVINCE - Putri, Maiza Dewita; Zulkarnain, Zulkarnain; Kusai, Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT   This research was conducted in May 2019 which is located in West Bagan Village, Bangko District, Rokan Hilir Regency, Riau Province.The method used in this study is a survey method with 36 respondents and asimple random sampling technique is used to determine the sample o the research.This research aims to find out the factors that cause poverty and to identify the strategies carried out by fishermen in dealing with poverty.Factors that cause poverty in fishermen are influenced by the Quality of Human Resources, which is low levels of education are indicators of low Quality of Human Resources. This indicator greatly determines a person or group of people who are poor or not poor.In addition, other factors that cause poverty are Simple Fishing Tools, and Fishermen Household Income and Expenditure Levels.The Strategy for fishermen household to survive in facing poverty in the form of efforts made to overcome the problems faced in meeting the food and non-food needs of the household.              Keywords: Poverty, Strategy, Survival, Fishermen